An inquiry into the learning-style and knowledge-building preferences of interior architecture students. (May 2016) - Demirkan, Halime
Abstract : This study explores the learning-style and knowledge-building preferences of interior architecture students using Felder–Soloman's Index of Learning Styles. Considering the learning and knowledge-building skills of students in design education, this study concludes that the instructor should not only be a conveyor of knowledge but also a facilitator. The findings indicate that design students' preferred learning styles are as follows, in descending order: Sensing/Intuitive, Visual/Verbal, Active/Reflective and Sequential/Global. In the two-way analysis, where the student's design studio grade was the dependent variable, significant effects were obtained for each scale. Furthermore, double interactions were highly significant between the Active/Reflective and Sensing/Intuitive scales and between the Active/Reflective and Sequential/Global scales. Highlights: Design students prefer to learn facts and data instead of concepts and theories. Design students prefer visual information and remember as visual pictures. Design students depict social oriented behaviour and learn best by doing. Significant interactions occur among thinking and learning style scales. Design teaching methods should address students' learning experiences.